The Impact of SGLT2 Inhibitor Dapagliflozin on Adropin Serum Levels in Men and Women with Type 2 Diabetes Mellitus and Chronic Heart Failure - Berezin, A. A.; Obradovic, Z.; Fushtey, I. M.; Berezina, T. A.; Novikov, E. V.; Schmidbauer, L.; Lichtenauer, M.; Berezin, A. E.; Фуштей, Іван Михайлович; Березін, Олександр Євгенійович (My University, 2023)
Background: adropin plays a protective role in cardiac remodeling through supporting energy metabolism and water homeostasis and suppressing inflammation. Low circulating levels of adropin were positively associated with the risk of cardiovascular diseases and type 2 diabetes mellitus (T2DM). We hypothesized that sodium–glucose linked transporter 2 (SGLT2) inhibitor dapagliflosin might represent cardiac protective effects in T2DM patients with known chronic HF through the modulation of adropin levels. Methods: we prospectively enrolled 417 patients with T2DM and HF from an entire cohort of 612 T2DM patients. All eligible patients were treated with the recommended guided HF therapy according to their HF phenotypes, including SGLT2 inhibitor dapagliflozin 10 mg, daily, orally. Anthropometry, clinical data, echocardiography/Doppler examinations, and measurements of biomarkers were performed at the baseline and over a 6-month interval of SGLT2 inhibitor administration. Results: in the entire group, dapagliflozin led to an increase in adropin levels by up to 26.6% over 6 months. In the female subgroup, the relative growth (D%) of adropin concentrations was sufficiently higher (D% = 35.6%) than that in the male subgroup (D% = 22.7%). A multivariate linear regression analysis of the entire group showed that the relative changes (D) in the left ventricular (LV) ejection fraction (LVEF), left atrial volume index (LAVI), and E/e’ were significantly associated with increased adropin levels. In the female subgroup, but not in the male subgroup, DLVEF (p = 0.046), DLAVI (p = 0.001), and DE/e’ (p = 0.001) were independent predictive values for adropin changes. Conclusion: the levels of adropin seem to be a predictor for the favorable modification of hemodynamic performances during SGLT2 inhibition, independent ofN-terminal brain natriuretic pro-peptide levels.
Keywords: type 2 diabetes mellitus; heart failure; hemodynamics; dapagliflosin; adropin; natriuretic peptide